What Christ Does, God Does: Surveying Recent Scholarship on Christological Monotheism - Smith, Brandon D. (Currents in biblical research, 2019)
Wilhelm Bousset's Kyrios Christos, which argued that 'high' Christology developed in the early church due to influences from Hellenism, was and still is a pivotal book in studies on early Christology. Martin Hengel, however, rebutted Bousset's sharp distinction with his own important insight-that early 'high' Christology actually developed out of Christians' Palestinian-Jewish heritage, wherein the church confessed and worshiped Jesus as divine alongside the one God of Israel. This article will survey the torchbearers of this debate, particularly noting the major ideas and contributors to the ongoing conversation about the 'Jewishness' and modes of divinity in early Christology.